PENGARUH LIKUIDITAS TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN TECHNOLOGY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2016-2020 - Ningrum, Fitria Puspa; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Stock return is the value obtained as a result of investment activities. The expected return is in the form of dividends for stock investments and interest income for investments in debt securities. The existence of a fairly high stock return will attract more investors to buy the stock. The purpose of this study was to determine the effect of liquidity on stock returns through profitability as an intervening variable in technology companies listed on the Stock Exchange for the period 2016-2022. The method used in this study is a descriptive and quantitative method. The population of this study are technology companies listed on the Indonesia Stock Exchange. The sampling technique was determined by purposive sampling method. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that liquidity has a positive but not significant effect on profitability, liquidity has a significant negative effect on stock returns, profitability has a positive significant effect on stock returns, liquidity has a positive but not significant effect on stock returns through profitability.